ANALISIS HASIL PENGELOLAAN TANAMAN JAGUNG UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT KECAMATAN SUELA - M. Juaini; Badarudin Badarudin; Muhammad Khairul Wazni Muhammad Khairul Wazni (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine how the maize crop management results can improve the welfare of the community in Suela District, and to determine the impact of the maize crop management pattern to improve the community welfare in Suela District. The results of the study show: first, in the results of corn crop management several management activities are carried out, namely preparation, implementation of supervision, harvest and post-harvest. Management of corn plants is carried out to minimize the occurrence of a loss to corn production. Second, the impact of corn management patterns to improve people's welfare seen from the level of welfare according to BPS includes household income, expenditure or consumption, living conditions, household facilities, health of family members, ease of obtaining health services, and ease of entering children into education levels. Based on the results of the analysis of the management results of corn plants, it is known that the level of community welfare in Suela District is at a high level of 90% and a medium level of 10%.